Occupational Burnout in Special Education: Social Support and Isolation as Moderating Factors - Okezi, Bilenko; Kennedy, Alexander (Journal of Research in Vocational Education, 2025)
This study investigates the relationship between turnover intentions, emotional exhaustion, social support, and professional isolation among special and regular educators in India using a quantitative approach. A sample of 173 teachers (special and regular educators) was assessed using validated scales, including the Maslach Burnout Inventory, Multidimensional Scale for Perceived Social Support, UCLA Loneliness Scale, and Turnover Intention Scale. Findings indicate that special educators experience significantly higher emotional exhaustion, professional isolation, and turnover intentions, whereas regular educators report greater social support. Addressing these challenges is crucial for reducing turnover rates and enhancing teacher well - being.